The impact of fruit and vegetable waste on economic loss estimation - B. Parsafar; M. Ahmadi; Gh.R. Jahed Khaniki; N. Shariatifar; A. Rahimi Foroushani (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Receiving nutrients from fruits and vegetables are essential for public health. However, a large amount of waste is produced during producing, supplying, and consuming these fruits and vegetables. Water, fertilizers and pesticides used for the production of agricultural products can affect the soil and their cultivation environment and finally lead to environmental pollution. Therefore, this study aimed to investigate the amount of fruit and vegetable waste caused by corruption and evaluate its economic loss and health damage.METHODS: The data were collected using the observation technique aided by observation tools and weighing tests to physically analyze and determine the quantity and quality of waste from Tehran’s fruit and vegetable distribution centers. In each center, the waste obtained from fruits and vegetables was stored in special waste tanks at the end of the day, and the waste was transported to outside the center by special waste disposal vehicles. The economic loss of unusable fruits and vegetables was calculated according to the weight of their waste in the fields of agricultural product supply. The data were analyzed using statistical software SPSS, ANOVA statistical test, and Excel software.FINDINGS: The results revealed that the amounts of fruit and vegetable wastes were 12 percent and 24 percent, respectively, accounting for a total loss of 54,891,539 USD. The highest quantity of fruit waste (15 percent) was observed in summer, and the economic loss due to fruit waste was higher in this season. Also, the amounts of vegetable waste in summer and spring were equal to 28 percent and 24 percent, respectively, indicating the higher economic loss due to vegetable in these seasons.CONCLUSION: The results showed that the economic loss due to vegetable waste was greater than the economic loss due to fruit waste. The amount of vegetable waste was 24 percent, representing a high economic loss. The generation and disposal of these wastes caused a great economic loss and health problems due to their unpleasant odor, release of leachate into the environment, and landfill pollution. Therefore, it was recommended to follow appropriate production principles and supply operations. Moreover, a comprehensive waste disposal management, as a practical measure, should be used to prevent and control these problems. The use of modern technology in harvesting, transporting and supplying fruits and vegetables could reduce their lesion, and subsequently reduce the economic loss.